Persistence of Brucella abortus in the Bone Marrow of Infected Mice - Cristina Gutiérrez-Jiménez; Lisiena Hysenaj; Alejandro Alfaro-Alarcón; Ricardo Mora-Cartín; Vilma Arce-Gorvel; Edgardo Moreno; Jean Pierre Gorvel; Elías Barquero-Calvo (Journal of Immunology Research)
Brucellosis is a zoonotic bacterial infection that may persist for long periods causing relapses in antibiotic-treated patients. The ability of Brucella to develop chronic infections is linked to their capacity to invade and replicate within the mononuclear phagocyte system, including the bone marrow (BM). Persistence of Brucella in the BM has been associated with hematological complications such as neutropenia, thrombocytopenia, anemia, and pancytopenia in human patients. In the mouse model, we observed that the number of Brucella abortus in the BM remained constant for up to 168 days of postinfection. This persistence was associated with histopathological changes, accompanied by augmented numbers of BM myeloid GMP progenitors, PMNs, and CD4+ lymphocytes during the acute phase (eight days) of the infection in the BM. Monocytes, PMNs, and GMP cells were identified as the cells harboring Brucella in the BM. We propose that the BM is an essential niche for the bacterium to establish long-lasting infections and that infected PMNs may serve as vehicles for dispersion of Brucella organisms, following the Trojan horse hypothesis. Monocytes are solid candidates for Brucella reservoirs in the BM.